Biomechanical changes in the gastrocnemius medius–Achilles tendon complex in people with hypermobility spectrum disorders: A cross-sectional compression sonoelastography study - Alsiri, Najla; Palmer, Shea (Frontiers in Medicine, 2023)
Objective: This study aimed to assess the biomechanical impact of Hypermobility Spectrum Disorders (HSD) on the elasticity of the gastrocnemius medius-Achilles tendon (GM-AT) complex. Methods: Using a cross-sectional design, the GM-AT complex elasticity was compared using sonoelastography (SEG) in an HSD group and healthy controls during rest and maximal isometric plantar flexion contraction. Results: The HSD group comprised 28 patients (26 women); mean ± SD age 28.7 ± 8.4 years, compared to 28 controls (26 women); 31.5 ± 8.7 years. During rest, greater elasticity was identified in HSD relative to controls at the GM-AT musculotendinous junction (strain ratio 2.05 ± 1.31 vs. 1.48 ± 0.49), mid-AT (3.60 ± 1.97 vs. 2.66 ± 1.00), and distal AT (4.57 ± 2.69 vs. 3.22 ± 1.94) (all p<0.05). During contraction, no significant differences were found between groups at the GM-AT musculotendinous junction (3.40 ± 2.16 vs. 2.62 ± 1.07), mid AT (10.75 ± 5.29 vs. 8.49 ± 3.53) or distal AT (8.55 ± 5.39 vs. 8.83 ± 3.51) (all p>0.05). No significant differences were found between groups in the GM strain ratio during rest (4.05 ± 1.43 vs 3.62 ± 0.78), or contraction (4.23 ± 1.29 vs 4.19 ± 1.31). Exploratory Receiver Operator Characteristics curve analysis suggested low sensitivity and specificity of the strain ratio for the diagnosis of HSD. Conclusion: People with HSD have greater GM-AT complex elasticity. Although statistically significant group differences were identified, further research is required to establish the diagnostic, clinical and research utility of strain ratio measurements.